Borrow with Sorrow? The Changing Risk Profile of Sub-Saharan Africa's Debt - Calderon, Cesar; Zeufack, Albert G. (World Bank, Washington, DC, 2020)
In the post-global financial crisis period, the financing of countercyclical policies led not only to a reduction in the fiscal surpluses across Sub-Saharan African countries, but also an increase in their levels of indebtedness. Although public debt for the region in 2018 was still below that of the pre-debt forgiveness period, the risk profile of public debt has sharply increased. The share of concessional public debt has been declining while that owed to private creditors and non–Paris Club bilateral creditors has been rising. The resulting reconfiguration of public debt has led to increased debt service in the region. Hence, the higher risk profile of debt and rising payments might lower the threshold for debt distress in the region. Addressing public debt vulnerabilities requires the buildup of external and fiscal buffers by conducting prudent fiscal policies and implementing growth-enhancing reforms, and the strengthening of debt management practices. However, the policy toolkit can be enlarged by gradually moving from debt management to balance-sheet management of the public sector, and policies to boost the efficiency of public investment.